Correlation of serum Nitric Oxide and hs-CRP in non-smoker and non-diabetic patients with Coronary Artery Disease - Khaki-Khatibi, Fatemeh; Ghojazadeh, Morteza; Javan, Naser; Yaghoub, Alireza (JOURNAL OF ADVANCES IN BIOLOGY, 2014)
Back ground: The nitric oxide (NO) decrease and inflammation are cooperative events involved in atherosclerosis development. In the present study we assessed the correlation of NO with high sensitive c- reactive protein (hs-CRP) in the patients with coronary artery disease (CAD). Significant risk factors such as cigarette and diabet were excluded from the study. Methods: One hundred sixty subjects including 80 patients with angiographically diagnosed CAD and 80 age and sex matched CAD-free subjects as control were studied. The levels of NO in the samples were measured with the Griess method. Hs-CRP was measured by Commercial Kit (PARS AZMON.IRAN) by ImmunoTorbidometry. Results: Comparing with the control reduced levels of NO was noticed in the patient group (p=0.02) and the serum hs-CRP levels were increased significantly as compared to controls (p=0.001). In patient group was reverse correlation between NO with hs-CRP, but this correlation was not significant (p=0.23). In control group was direct correlation between NO with hs-CRP, but this correlation was not significant (p=0.33). Conclusion: It is concluded that, in patients with stable coronary artery disease, low grade systemic inflammation is associated with increased in vivo oxidative stress leading to impaired systemic bioavailability of nitric oxide.